59.0k views
4 votes
Solve the equation. - 4(r + 6) = -54

2 Answers

2 votes

- 4(r + 6) = -54​

expand

-4r - 24 = -54

add 24 to both sides

-4r = -54 + 24

-4r = -30

Divide both sides by -4

r = -30/-4

r = 7.5

User Graham
by
5.6k points
4 votes

Answer:


\boxed{\sf{r=(15)/(2)=7.5 }}

Explanation:

Use the distributive property.

a(b+c)=ab+ac

-4(r+6)=-54

Isolate the term of r from one side of the equation.

You have to divide by -4 from both sides.


\sf{(-4\left(r+6\right))/(-4)=(-54)/(-4)}

Solve.

-54/-4=27/2

r+6=27/2

Subtract by 6 from both sides.

r+6-6=27/2-6

Solve.


\sf{-(6* \:2)/(2)+(27)/(2)}}

-6*2+27/2

Remember to solve this problem, first thing you do is solve with order of operations.

PEMDAS stands for:

  • Parentheses
  • Exponents
  • Multiply
  • Divide
  • Add
  • Subtract

Do multiply first.

-6*2=-12

-12+27

Then add or subtract the numbers from left to right.

-12+27=15

r=15/2

Divide is another option.

15/2=7.5


\rightarrow \boxed{\sf{r=(15)/(2)=7.5}}

Therefore, the correct answer is r=15/2=7.5.

I hope this helps, let me know if you have any questions.

User Ryan Stanley
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.